“STUDY OF BRAND PROMOTION STRATEGY WITH REFERENCE TO AMAZON AND FLIPKART: TWO MAJOR PLAYERS IN THE E-COMMERCE INDUSTRY” - Rathore, Alok (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
The rapid evolution of e-commerce has transformed the retail landscape, with Amazon and Flipkart emerging as leading players in the global and Indian markets, respectively. In order to better understand how Amazon and Flipkart's unique marketing techniques affect market share, consumer behaviour, and competitive positioning, this study compares and contrasts them. Amazon is a multinational-commerce behemoth that uses data analytics, a vast technology infrastructure, and a customer-focused strategy to dominate markets all over the world. Conversely, Flipkart leverages its profound comprehension of the Indian market by prioritizing customized offerings, strategic alliances, and specialized strategies to meet regional tastes. By carefully analysing crucial components including branding, consumer interaction, digital marketing, and promotional methods, this study analyses the marketing strategies of the two businesses. Amazon has a strong focus on innovation and technology developments, as evidenced by the wide range of   products it offers and the smooth integration of its Prime membership program. Flipkart, on the other hand, has a marketing plan that is specifically designed to meet  the demands and obstacles of the Indian market. The organization hopes to appeal to a wide range of customers by emphasizing regional festivals, specialized advertising, and vernacular languages. While Amazon's strategy emphasizes scalability and global consistency, Flipkart’s approach is deeply rooted in regional customization and consumer engagement. The study also explores how these strategies impact customer loyalty, brand perception, and market performance.